Carta de José Tous Soto a Roberto H. Todd - Todd, Roberto H.; Tous Soto, José (My University, 1922)
Pleito electoral.
Keywords: Elections--Puerto Rico--History.; Puerto Rico--Política y gobierno.; Puerto Rico--Politics and government.